Iron overload induces BMP6 expression in the liver but not in the duodenum - Léon Kautz; Céline Besson-Fournier; Delphine Meynard; Chloé Latour; Marie-Paule Roth; Hélène Coppin (Haematologica, 2011)
Background The bone morphogenetic protein BMP6 regulates hepcidin production by the liver. However, it is not yet known whether BMP6 derives from the liver itself or from other sources such as the small intestine, as has been recently suggested. This study was aimed at investigating the source of BMP6 further.Design and Methods We used three different strains of mice (C57BL/6, DBA/2, and 129/Sv) with iron overload induced either by an iron-enriched diet or by inactivation of the Hfe gene. We examined Bmp6 expression at both the mRNA (by quantitative PCR) and protein (by immunohistochemistry and Western blotting analyses) levels.Results We showed that iron overload induces Bmp6 mRNA expression in the liver but not in the duodenum of these mice. Bmp6 is also detected by immunohistochemistry in liver tissue sections of mice with iron overload induced either by an iron-enriched diet or by inactivation of the Hfe gene, but not in liver tissue sections from iron-loaded Bmp6-deficient mice. Bmp6 in the duodenum was below immunodetection threshold, thus confirming quantitative PCR data. Lack of specificity of available antibodies together with slight heterogeneity between 129 substrains may account for the differences with previously published data.Conclusions Our data strongly support the importance of liver BMP6 for regulation of iron metabolism. Indeed, they demonstrate that intestinal Bmp6 expression is modulated by iron neither at the mRNA nor at the protein level.